INVESTIGATION OF ZINC HYDROXIDE CARBONATE FORMATION FROM ZINC NITRATE SOLUTION BY SODIUM CARBONATE PRECIPITATION - Hamdamov, A. A.; Ochilov , J.M.; Tavashov , Sh.Kh. (Journal for Technology and Science, 2026)
Objective: This study presents the results of zinc hydroxide carbonate production through precipitation from a zinc nitrate solution using an 18% sodium carbonate solution. Method: The effects of key process parameters on the precipitation efficiency were systematically examined, and optimal operating conditions were determined. Results: The initial zinc nitrate solution contained 13,16% ZnO. The highest precipitation efficiency of zinc hydroxide carbonate was achieved within a pH range of 7,9–8,3 and at a temperature of 65–70°C. Additionally, extending the process duration from 40 to 45 minutes led to an increase in the precipitation degree from 98,79% to 99,96%. Novelty: The effects of key process parameters on the precipitation efficiency were systematically examined, and optimal operating conditions were determined.